2018
DOI: 10.3928/00220124-20180320-06
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rural Nurse Practitioner Knowledge About Polycystic Ovary Syndrome Through Continuing Education

Abstract: Continuing education presentations have the potential to increase rural NPs' knowledge about PCOS so they can provide evidence-based care to rural women with PCOS. J Contin Educ Nurs. 2018;49(4):164-170.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…4 Many previous studies have shown evidence of CME effectiveness in improving healthcare workers' knowledge, capacities or performance and patients' health outcomes. [5][6][7][8][9] However, the CME system also faces challenges, such as various needs or expectations from healthcare workers. [10][11][12][13][14][15] In China, unlike the USA, 16 Australia 17 18 and European countries, 19 there is not a complete CME system for healthcare workers, 2 20 21 let alone for rural healthcare workers (RHWs).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…4 Many previous studies have shown evidence of CME effectiveness in improving healthcare workers' knowledge, capacities or performance and patients' health outcomes. [5][6][7][8][9] However, the CME system also faces challenges, such as various needs or expectations from healthcare workers. [10][11][12][13][14][15] In China, unlike the USA, 16 Australia 17 18 and European countries, 19 there is not a complete CME system for healthcare workers, 2 20 21 let alone for rural healthcare workers (RHWs).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…While around 95% of physicians surveyed in the United States and Europe are aware of type 2 diabetes risk with PCOS, 9 40 examination of rural nurse practitioners in the United States observed that only ∼40% of the nurse practitioners recognized PCOS as a risk factor for type 2 diabetes mellitus. 48 Given their common clinical setting in family practice, internal medicine, and women's health, continued education for nurse practitioners on the diagnosis and comorbidities of PCOS may greatly reduce diagnostic delays and prevent comorbidities of PCOS. 48 A survey of 200 young nurses in Pakistan found that 40% had poor or no knowledge of PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…48 Given their common clinical setting in family practice, internal medicine, and women's health, continued education for nurse practitioners on the diagnosis and comorbidities of PCOS may greatly reduce diagnostic delays and prevent comorbidities of PCOS. 48 A survey of 200 young nurses in Pakistan found that 40% had poor or no knowledge of PCOS. 49 A recent qualitative study in allied health professionals (dietitians, physical therapists, and psychologists) from Australia explored their experience with the implementation of lifestyle recommendations since the 2018 International PCOS Guideline recommendations came into effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, evaluation questions were used in the studies conducted by Anderson (2014), Bednarczyk et al (2022), Johnson (2014), and Klein and Bindler (2022. Improved knowledge about continuing education topics was evident in participants of all intervention studies (Anderson, 2014;Bednarczyk et al, 2022;Boesl & Saarinen, 2016;Buriak et al, 2015;Carron et al, 2018;Choma & McKeever, 2015;Claiborne, 2016;Hessler, 2015;Hoffmann et al, 2018;Johnson, 2014;Klein & Bindler, 2022;Pietras et al, 2023;Roberts et al, 2022;Roberts et al, 2023). While some continuing education interventions were found to be high quality and usable (e.g.…”
Section: Continuing Education Interventions For Apn Rolesmentioning
confidence: 96%